Metabolite changes in blood predict the onset of tuberculosis - Weiner, January; Maertzdorf, Jeroen; Suliman, Sara; Hanekom, Willem A.; Mayanja-Kizza, Harriet; Kaufmann, Stefan H.E.; GC6-74 consortium (Nature communications, 2018)
New biomarkers of tuberculosis (TB) risk and disease are critical for the urgently needed control of the ongoing TB pandemic. In a prospective multisite study across Subsaharan Africa, we analyzed metabolic profiles in serum and plasma from HIV-negative, TB-exposed individuals who either progressed to TB 3–24 months post-exposure (progressors) or remained healthy (controls). We generated a trans-African metabolic biosignature for TB, which identifies future progressors both on blinded test samples and in external data sets and shows a performance of 69% sensitivity at 75% specificity in samples within 5 months of diagnosis. These prognostic metabolic signatures are consistent with development of subclinical disease prior to manifestation of active TB. Metabolic changes associated with pre-symptomatic disease are observed as early as 12 months prior to TB diagnosis, thus enabling timely interventions to prevent disease progression and transmission.
Keywords: Diagnostic markers, Metabolomics, Predictive medicine, Tuberculosis